LEISURE AND LABOR: BARRA NOVA, SÃO MATEUS CRAB CATCHERS - WHAT DO THEY THINK? (Fiep Bulletin - online, 2014)
The present study has the purpose of identifying the relationship between work and leisure related to the activities of the "crab catchers" of Nativo, Barra Nova, São Mateus, State of Espírito Santo, Brazil. The research has used the open-interview method with eight individuals, who live in the community, with the purpose of identifying the production process of crab catching and leisure options existing in the community. Analysis of discourse was used, as per Fiorin (1999). The individual discourse was summarized and interpreted and the concepts and categories were analyzed. A suspensive leisure was identified, because the individuals execute their work without the necessary determination and amount of energy required for professional labor.
Keywords: 1. Crab; 2. Barra Nova; 3. Labor; 4. Leisure